COMPOSITION CATCHES OF TAMBAN NETS IN LANJUT VILLAGE SINGKEP PESISIR DISTRICT LINGGA REGENCY RIAU ISLAND PROVINCE - Febry Astuti; Bustari Bustari; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe research aim to know composition of tamban nets based on species, weight (kg), individual, and know how the fish caught on the fishing nets . The research method used is survey method by doing direct observation of the tamban nets catch result and then the catch is identified to fish species, individual number and fish weight. The results of the descriptive analysis show that the main catches are tamban (sardinella allbella) with a weight of 151,2 kg (98,25%). By-catch consists of 5 species jarbua terapon (terapon jarbua), yellowstripe scad (selaruides leptolepis), blue mackerel (scomber australasicus), cucut fish (charcharinus sp), and fish sprawl (carangoides malabaricus) with a total weight of 2.7 kg (1.75%).Kata Kunci : Tamban nets , composition, Sardinella albella